Advanced antistatic composites for electrostatic Dissipation: Development of EPDM based conductive elastomeric nanocomposites - Habiba Tanveer; Shaista Taimur; Mujtaba Ellahi; Talha Baig; Nazeeha S. Alkayal; Ahsan Ali; Tariq Yasin; Wael A. Altabey; Mohammad Noori; Sallam A. Kouritem (Polymer Testing, 2025)
Electrostatic charge buildup is a prevalent challenge instigating safety risks and operational inefficiencies in different industrial sectors. The necessity for efficient electrostatic dissipation with reliable antistatic solution is a critical contest. This study reports for the first time the development of EPDM based elastomeric nanocomposites (ENCs) reinforced by novel electrically conducting grafted polymeres specifically, polyaniline grafted sepiolite (ENC1), polyaniline grafted graphene oxide (ENC2), and polyaniline grafted sepiolite/reduced graphene oxide (ENC3), offering a significant electrostatic dissipation capability. This novel approach not only enhances the conductivity of the rubber but also opens new avenues for applications in various industries requiring antistatic properties. Compositional analyses are carried out by Raman and FTIR spectroscopy. Morphological studies by SEM indicate the homogeneous distribution of fillers in continuous EPDM matrix. Thermogravimetric analysis demonstrated that the developed nanocomposites exhibited thermal stability up to 350 °C, attributed to the incorporation of thermally stable conductive fillers. The electrical and mechanical properties were investigated for their potential use as antistatic materials. The minimum surface resistivity (65 × 103Ω/·) and antistatic half-life (τ1/2, 0.000005 s) validates their application as antistatic material to prevent sensitive electronic devices from charge accumulation. The maximum tensile strength of 51 MPa and elongation at break of 247 % was observed. The maximum cross-link density (ϑ) of 4.0 × 10−2 mol/cc is shown by ENC3. The hydrophobic nature of EPDM sheets was investigated by water contact angle and water absorption %. The insights of this study provide the acumen of next-generation novel grafted polymer filler-based elastomeric nanocomposites for antistatic/electrostatic dissipative applications along with enhanced durability, environmental sustainability, and innovative industrial utility.